PENGEMBANGAN KARTU PETUALANGAN SEBAGAI MEDIA PROMOSI KESEHATAN UNTUK MENINGKATKAN KEDISIPLINAN MENYIKAT GIGI PADA ANAK - Rejeki, Putri; Prasetya, Mia Ayustina; Anggaraeni, Putu Ika; Aprillia, Rika (Universitas Udayana, 2023)
Introduction: The behavior of teeth brushing with the correct method in Indonesian people is still relatively low at 2.8%, causing an increase in dental and oral problems from 43.3% in 2007 to 57.6% in 2018. The most dental and oral problems by age are in the age group 5-9 years (51.72%). Efforts to improve children’s behavior in maintaining their dental health require health promotion education with interesting and appropriate methods for children. This study aims to develop